Patterns of empathy in online communication - Pheil, Ulrike; Zaphiris, Panayiotis (My University, 2007)
This article presents an investigation of empathy within an online community for older people (SeniorNet). Qualitative content analysis of 400 messages from a discussion board about depression was used to determine how empathy is expressed and facilitated in online communication. Special emphasis was placed on determining the components of online empathy. A code scheme that we developed to analyse online empathy is also presented. The findings were compared to offline studies about empathy in order to investigate the influence that the mediating technology has on the phenomenon.